2017
DOI: 10.1002/jrs.5276
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of Ni1‐XZnXFe2O4 nanopowders

Abstract: In this paper, we present the results of studies the Raman spectra of Ni1‐xZnxFe2O4 (x = 0, 0.25, 0.4, 0.5, 0.6, 0.75, 1.0) ferrites nanopowders at room temperature and spectral range from 50 to 2,000 cm−1. The interpretations of the Raman spectra are given. The analysis of the results showed that spectra of compositions contain of maxima interpreted by us as oscillations of magnetic sublattices. The intensities of these maxima correlated with changes of Ni and Zn concentrations in compositions and, accordingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
(60 reference statements)
1
4
0
Order By: Relevance
“…† The observed Raman modes are in good agreement with the literature reports. 38 In the Ni600 nanoparticle sample, the peaks centered on 216, 274 and 397 cm À1 could be attributed to A 1g , E g (1) and E g (2) vibrational modes of hematite a-Fe 2 O 3 , 39 respectively, which is consistent with the results of the XRD. No additional peak corresponding to any other iron oxide phase is present for the other compounds, thus conrming the monophasic composition throughout.…”
Section: Raman Analysissupporting
confidence: 83%
“…† The observed Raman modes are in good agreement with the literature reports. 38 In the Ni600 nanoparticle sample, the peaks centered on 216, 274 and 397 cm À1 could be attributed to A 1g , E g (1) and E g (2) vibrational modes of hematite a-Fe 2 O 3 , 39 respectively, which is consistent with the results of the XRD. No additional peak corresponding to any other iron oxide phase is present for the other compounds, thus conrming the monophasic composition throughout.…”
Section: Raman Analysissupporting
confidence: 83%
“…Raman spectrum of calcined ZFO particles shown in Figure 1 (d) reveals the presence of five Raman active modes (A1g+Eg+3F2g) which arise from the motion of O ions within the spinel structures [28–30] . The band observed at 213–243 cm −1 , corresponding to the F2g (1) active mode, is attributed to translational movements of the entire ZnO 4 tetrahedra.…”
Section: Resultsmentioning
confidence: 97%
“…[28] Raman spectrum of calcined ZFO particles shown in Figure 1 (d) reveals the presence of five Raman active modes (A1g + Eg + 3F2g) which arise from the motion of O ions within the spinel structures. [28][29][30] The band observed at 213-243 cm À 1 , corresponding to the F2g (1) active mode, is attributed to translational movements of the entire ZnO 4 tetrahedra. The band within the range of 334-352 cm À 1 , associated with the Eg active mode, represents symmetric bending vibrations of O atoms in tetrahedral (A) site.…”
Section: Resultsmentioning
confidence: 99%
“…Aliyeva et al have described the Raman spectra of of Ni 1−x Zn x Fe 2 O 4 (x = 0, 0.25, 0.4, 0.5, 0.6, 0.75, 1.0) ferrite nanopowders at room temperature and spectral range from 50 to 2,000 cm −1 . The interpretation of the Raman spectra showed that compounds that contain maxima can be interpreted as oscillations of magnetic sublattices . Arakcheev and co‐workers presented a spectroscopic characterization of adsorbate confined in small mesopores to distinguish first surface‐adsorbed layer, polymolecular layers, and liquid clusters .…”
Section: Nanomaterialsmentioning
confidence: 99%
“…The interpretation of the Raman spectra showed that compounds that contain maxima can be interpreted as oscillations of magnetic sublattices. [106] Arakcheev and co-workers presented a spectroscopic characterization of adsorbate confined in small mesopores to distinguish first surface-adsorbed layer, polymolecular layers, and liquid clusters. [107] Arya and co-workers described the enhancement of Raman scattering intensity using a photonic nanojet of portable and reusable single lollipop-shapted microstructures.…”
Section: Carbon Nanotubes Carbon Materials Graphene Layered Solimentioning
confidence: 99%